“Holy Moly!” Positive and Negative Connotations of Swear Words in A Popular Western Animated Movie - Kismullah Abdul Muthalib; Ika Apriani Fata; Zahra Nuzula (Indonesian Journal of EFL and Linguistics, 2022)
The use of swear words is common and even popular in movies for adult viewers. However, misunderstanding and ignorance of the intended viewers can cause younger viewers to be exposed to movies with various profanities. The Simpsons, an animated movie, is a good example of this phenomenon. This animated movie is known to contain obscene language expressions which can be mistakenly assumed to be intended for younger viewers. This study sought to identify the kinds and purposes of expletives used in The Simpsons. The current study used Hughes’ framework to analyze the types of swear words, and Andersson and Trudgill's framework was used to analyze their functions. Data were gathered from seven episodes drawn from different seasons of the animated series. Of 102 swear words found in the dialogues of the episodes, seven types of swear words were identified, including anatomical insult, excrement, sexual intercourse, personal background, mental illness, animal term, and religious oath. Additionally, four swearing meanings and functions were discovered abusive, auxiliary, expletive, and humorous. Therefore, it is expected that general readers will express themselves more thoughtfully, be able to identify the target audience for movies, and make more informed decisions when choosing movies for younger audiences.